Negotiation Of Islam And Local Culture In Traditional Lampung Marriage - Kesuma, Arsyad Sobby; Hakiki, Kiki Muhamad; Shomad, Bukhori Abdul (AL-ADYAN, 2022)
This article examines two types of Lampung communities, Pepadun and Saibatin, which have interesting differences, especially in the context of their traditional marriages. Both Lampung Pepadun and Saibatin are unique in terms of their customs, traditional dress and marriage process. However, the focus of this article is on how Islamic symbolic values are reflected in the marriage ceremony of the Lampung Pepadun community. The research findings show: 1). The Lampung Pepadun community has three types of marriage, namely honest marriage, semanda marriage, and pineng ngerabung sanggar marriage. 2). The relationship between Islam and Lampung culture can be considered as an inseparable entity, where Islam that developed in Lampung was influenced by its local culture, while Lampung culture also experienced a rich influence from Islamic values. As a result, the combination of the two resulted in a syncretic culture with its own characteristics.